2007
DOI: 10.1128/mcb.02238-06
|View full text |Cite
|
Sign up to set email alerts
|

Function of a Conserved Checkpoint Recruitment Domain in ATRIP Proteins

Abstract: The ATR (ATM and Rad3-related) kinase is essential to maintain genomic integrity. ATR is recruited to DNA lesions in part through its association with ATR-interacting protein (ATRIP), which in turn interacts with the single-stranded DNA binding protein RPA (replication protein A). In this study, a conserved checkpoint protein recruitment domain (CRD) in ATRIP orthologs was identified by biochemical mapping of the RPA binding site in combination with nuclear magnetic resonance, mutagenesis, and computational mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(168 citation statements)
references
References 51 publications
5
160
1
2
Order By: Relevance
“…1C). We found that in reaction mixtures that were of low ionic strength, ATR phosphorylated Chk1 in a manner virtually dependent on TopBP1, which is in agreement with previous reports (14,20) (Fig. 2, lane 3).…”
Section: Resultssupporting
confidence: 93%
“…1C). We found that in reaction mixtures that were of low ionic strength, ATR phosphorylated Chk1 in a manner virtually dependent on TopBP1, which is in agreement with previous reports (14,20) (Fig. 2, lane 3).…”
Section: Resultssupporting
confidence: 93%
“…4 and 5) are consistent with a role for RPA70N-HDHB interaction in recruiting HDHB to chromatin. Although technical difficulties have so far confounded our efforts to directly demonstrate the importance of these motifs in recruiting HDHB to chromatin, the interaction closely resembles that of RPA70N with ATRIP, Rad9, and Mre11 (28,33,50). Qualitatively, acidic peptides from each of these proteins have been shown to bind specifically to the same surface of RPA70N that binds the acidic peptide from HDHB (33).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids used for bacterial expression of His-tagged RPA truncation mutants were: pET15b-RPA70 (aa 1-120) for RPA70N (28) from Dr. C. Arrowsmith, pET15b-RPA32 (aa 172-270) for RPA32C (29), pET11d-RPA70 (aa 1-168) for RPA70NϩL (30) from Dr. M. Wold, pET15b-RPA70 (aa 181-422) for RPA70AB (31), and pET15b-RPA70 (aa 436 -616/32 (aa 43-171)/14) for RPA70C/ 32D/14 (32), both from Dr. A. Bochkarev.…”
Section: Methodsmentioning
confidence: 99%
“…The single-stranded DNA is then coated by replication protein A (RPA) (Walter and Newport 2000;Byun et al 2005), which signals the independent recruitment of two checkpoint complexes: the ataxia-telangiectasia mutated (ATM)-Rad3-related kinase-ATR-interacting protein (ATR-ATRIP) complex and the Rad9-Hus1-Rad1 (9-1-1) complex. The ATRIP-ATR complex is bound to DNA by a direct interaction between ATRIP and RPA Ball et al 2005Ball et al , 2007Kim et al 2005;Namiki and Zou 2006). In contrast, loading of the 9-1-1 complex requires several steps.…”
mentioning
confidence: 99%